A multidisciplinary assessment of 320 athletes with long-standing groin pain syndrome in keeping with the Italian consensus agreement: the high incidence and the multiple causes of inguinal and hip pathologies and pubic osteopathy - Bisciotti, G. N.; Auci, A.; Bona, S.; Bisciotti, A.; Cassaghi, G.; Eirale, C.; Panascì, M.; Parra, F.; Zini, R. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Groin pain syndrome is an important and increasing problem in numerous sports (e.g. soccer, football, ice hockey, handball and rugby). Long-standing groin pain syndrome is a form of groin pain syndrome in which the cohort of symptoms reported by the patient is experienced for a long period, typically for over 12 weeks, and is recalcitrant to any conservative therapy. Long-standing groin pain syndrome is potentially career-ending for elite athletes. METHODS: A descriptive epidemiological study was carried out on 320 athletes (290 men and 30 women) affected by long-standing groin pain syndrome, following the Guidelines issued by the Groin Pain Syndrome Italian Consensus Conference on terminology, clinical evaluation and imaging assessment of groin pain in athlete. RESULTS: Amongst the clinical tests for inguinal pathologies, only the External Inguinal Ring Exploration proved conclusive (sensitivity: 0.97; specificity: 0.95; positive predictive value: 0.98; negative predictive value: 0.90; likelihood ratio: 19.4). In testing for adductor tendinopathies, only the Isometric Squeeze with flexed knee and distal resistance (sensitivity: 0.86; specificity: 0.45; positive predictive value: 0.48; negative predictive value: 0.85; likelihood ratio: 5.7) and the Palpatory Test at the pubic insertion of the adductor longus (sensitivity: 0.93; specificity: 0.89; positive predictive value: 0.96; negative predictive value: 0.79; likelihood ratio: 8.5) proved, respectively, useful at times and moderately useful. Among the tests for hip pathologies, only the Flexion Abduction External Rotation Test was seen to be conclusive (sensitivity: 0.90; specificity: 0.93; positive predictive value: 0.98; negative predictive value: 0.72; likelihood ratio: 12.9). In the male population on average, long-standing groin syndrome presents either a single cause or multiple causes in respectively 74% and 26% of cases. Furthermore, almost 58% of all cases traced to a single clinical cause can be attributed to inguinal pathologies alone. Long-standing groin syndrome in the female population shows only one pathological cause with inguinal pathologies, and acetabular labrum tear representing the most frequent etiologies. CONCLUSIONS: Men and women exhibit different causes for long-standing groin pain syndrome. Several routine tests used in the clinical evaluation of this condition furnish a low likelihood ratio. Consequently, in order to optimize clinical evaluation and minimize patient discomfort, clinical evaluation should be based on tests with a greater likelihood ratio.